Statistical Analysis of the Leadership Perceptions in a Public Administration Office - Sousa, Áurea Sandra Toledo de; Batista, Maria da Graça; Arruda, Ana Carolina (Global Disclosure of Economics and Business, 2015)
The main purpose of this paper is to identify and characterize the leadership features in a public administration office of the Azores (Autonomous Region of the Azores), in orders to verify the existence or not of a positive leadership based on the employees’ perceptions. The main conclusions are attained using data gathered via a previously tested and validated questionnaire. Overall, we conclude that subordinates don’t consider that their leaders show behaviors that they can associate with a totally positive and effective leadership although they are pleased with the fact that they are not extremely controllers and that they seek to do what the majority of the subordinates wants.